(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The aquatic plant Euryale ferox’s seeds, known as foxnuts, have drawn attention recently because of its distinctive nutritional makeup, therapeutic benefits, and commercial importance. The goal of this review article is to give a thorough overview of foxnuts, including information on their nutritional value, health advantages, traditional usage, and economic significance. A great supply of proteins, dietary fibre, minerals, and antioxidants may be found in foxnuts. They are highly regarded in particular for their low-fat content and distinctive starch composition, which makes them an advantageous nutritional option for anyone looking for low-calorie, nutrient-dense meals. They may have health-promoting qualities, such as antioxidant, anti-inflammatory, and anti-cancer benefits, due to the presence of bioactive substances such saponins and flavonoids. Foxnuts have a long history of usage in traditional medical systems like Ayurveda and Traditional Chinese Medicine (TCM), in addition to their nutritional benefits. These seeds are said to provide a number of health advantages, from increasing kidney health and boosting vitality to easing digestive problems and controlling blood sugar levels. The processes behind these health claims are beginning to be understood thanks to recent scientific studies. Additionally, foxnut commerce and cultivation have a considerable economic impact, particularly in areas where the plant is native. The study sheds light on foxnuts’ economic significance for regional economies and international trade networks by investigating their cultivation methods, worldwide production patterns, and market dynamics. A promising natural resource with exceptional nutritional, therapeutic, and commercial potential is foxnuts.